Motorcycle Parking Security System based on Website and QR Code Technology - Yuni, Riva Andra; Kasoep, Werman; Yolanda, Desta (Universitas Andalas, 2023)
The increase in motorcycle theft cases has become a serious concern. This research aims to design a motorcycle parking security system through a website in response to this challenge. The system uses a website accessible via smartphones using QR code. Users scan the provided QR code to access the website, where they will be prompted to enter a password that functions as a controller for the locking and unlocking process of the motorcycle's front wheel using a servo motor. Furthermore, to detect forced removal attempts, the system is equipped with an alarm that notifies the parking attendant. This alarm will be activated if vibrations above 20 cm/s2 are detected and will be accompanied by a buzzer sound as a danger signal. Based on the results of the study, this system can work well and produce the appropriate output as previously designed with a success percentage of 91% and the servo motor as a motorcycle safety device can work to lock the front tire of a motorcycle that has a tire tread width of 90 mm according to with what was previously defined